Sepsis caused by Anaerococcus nagyae after transarterial- chemoembolization for hepatocellular carcinoma: Case report and literature review - ÜLGER, NURVER (ELSEVIER SCI LTD, 2021)
Hepatocellular carcinoma (HCC) is more common in patients with chronic viral hepatitis infection and cirrhosis. Transarterial chemoembolization (TACE) is an effective treatment method for unresectable HCC. A rare complication of TACE is the development of bloodstream infection. We present a fatal case of sepsis due to Anaerococcus nagyae after TACE. (c) 2021 Elsevier Ltd. All rights reserved.
Keywords: Anaerococcus nagyae; Hepatocellular carcinoma; Transarterial chemoembolization; Sepsis; BACTEREMIA